Association Between Sleep-Disordered Breathing and Hypertensive Disorders of Pregnancy and Gestational Diabetes Mellitus. Issue 1 (January 2017) - Facco, Francesca L.; Parker, Corette B.; Reddy, Uma M.; Silver, Robert M.; Koch, Matthew A.; Louis, Judette M.; Basner, Robert C.; Chung, Judith H.; Nhan-Chang, Chia-Ling; Pien, Grace W.; Redline, Susan; Grobman, William A.; et al.
Abstract : OBJECTIVE: To estimate whether sleep-disordered breathing during pregnancy is a risk factor for the development of hypertensive disorders of pregnancy and gestational diabetes mellitus (GDM). METHODS: In this prospective cohort study, nulliparous women underwent in-home sleep-disordered breathing assessments in early (6–15 weeks of gestation) and midpregnancy (22–31 weeks of gestation). Participants and health care providers were blinded to the sleep test results. An apnea–hypopnea index of 5 or greater was used to define sleep-disordered breathing. Exposure–response relationships were examined, grouping participants into four apnea–hypopnea index groups: 0, greater than 0 to less than 5, 5 to less than 15, and 15 or greater. The study was powered to test the primary hypothesis that sleep-disordered breathing occurring in pregnancy is associated with an increased incidence of preeclampsia. Secondary outcomes were rates of hypertensive disorders of pregnancy, defined as preeclampsia and antepartum gestational hypertension, and GDM. Crude and adjusted odds ratios and 95% confidence intervals (CIs) were calculated from univariate and multivariate logistic regression models. RESULTS: Three thousand seven hundred five women were enrolled. Apnea–hypopnea index data were available for 3, 132 (84.5%) and 2, 474 (66.8%) women in early and midpregnancy, respectively. The corresponding prevalence of sleep-disordered breathing was 3.6% and 8.3%. The prevalence of preeclampsia was 6.0%, hypertensive disorders of pregnancy 13.1%, and GDM 4.1%. In early and midpregnancy the adjusted odds ratios for preeclampsia when sleep-disordered breathing was present were 1.94 (95% CI 1.07–3.51) and 1.95 (95% CI 1.18–3.23), respectively; hypertensive disorders of pregnancy 1.46 (95% CI 0.91–2.32) and 1.73 (95% CI 1.19–2.52); and GDM 3.47 (95% CI 1.95–6.19) and 2.79 (95% CI 1.63–4.77). Increasing exposure–response relationships were observed between apnea–hypopnea index and both hypertensive disorders and GDM. CONCLUSION: There is an independent association between sleep-disordered breathing and preeclampsia, hypertensive disorders of pregnancy, and GDM. Abstract : There is an independent association between sleep-disordered breathing during pregnancy and preeclampsia and gestational diabetes mellitus.Supplemental Digital Content is Available in the Text.